(untitled) (Global Journal of Medical Research, 2016)
Collective memory requires a shared experience and the deposition of the experience in a manner that can be recalled at a later time. Collective memory can be transmitted orally, stored in writings, films, museums and other memorial sites, and also in our DNA. Recent studies have demonstrated that humans, like all animals, are themselves collectives, consisting of the host and abundant and diverse symbiotic microorganisms. The total DNA of a human, referred to as the human hologenome, consists of about 19,000 host genes and eight million microbial genes. It is now accepted that the microbial genetic information plays an important part in the fitness and evolution of animals and plants. We discuss here how the hologenome, especially the microbial component, interacts with cultural memory and contributes to collective memory. One of the novel points is that the microbial gene pool responds to changes in the environment on the basis of the principle of use and disuse. As such, the microbiome is particularly wellsuited to serve as a vehicle for DNA-based collective memory.